Indian Involvement in Afghanistan: Stepping Stone or Stumbling Block to Regional Hegemony? - Melanie Hanif (German Institute of Global and Area Studies (GIGA), 2009)
Due to its geo-strategic location between the Central Asian, South Asian, and Middle Eastern security complexes, Afghanistan is often defined as an insulator state, and sometimes also as a connector. This in-between position has led to constant instability: ever since the creation of the Durrani Empire, the country has suffered from internal power struggles as well as outside interference. External attempts to control Afghanistan have nonetheless proven extremely difficult. This also holds true for the current conflict management efforts of the US-led coalition. But what could the alternatives be? This paper seeks to explore the prospect of regional security cooperation as a path towards stability for Afghanistan. Although the academic debate has thus far not considered Afghanistan as a primarily South Asian country, I will focus on the South Asian subsystem for three reasons: Firstly, current security matters in Afghanistan are highly connected to the situation in Pakistan. Secondly, with its accession to the South Asian Association for Regional Cooperation (SAARC), Afghanistan has shown an interest in establishing stronger ties with South Asia. Thirdly, India as a rising regional power is the only country in the region that might possess the capabilities, the willingness, and the legitimacy for a long-term engagement in Afghan security. – – Aufgrund seiner geostrategischen Lage zwischen Zentralasien, Südasien und dem Nahen Osten wird Afghanistan oftmals als Pufferstaat, manchmal auch als Brücke zwischen diesen Regionen definiert. Diese Position war mit anhaltender Instabilität verbunden: Seit der Gründung des Durrani-Imperiums hat das Land unter internen Machtstreitigkeiten ebenso gelitten wie unter externer Einmischung. Versuche, das Land unter Kontrolle zu bekommen, stellten sich für externe Mächte allerdings als äußerst schwierig heraus. Dies trifft auch auf die gegenwärtigen Unternehmungen der internationalen Gemeinschaft zu, die darauf abzielen, Afghanistan zu befrieden. Der vorliegende Beitrag konzentriert sich auf die bislang wenig diskutierte Frage, unter welchen Umständen eine regionale Kooperation in Sicherheitsfragen eine Alternative zu den internationalen Stabilisierungsversuchen bietet. Der Schwerpunkt liegt dabei auf Südasien, da 1. die Sicherheitsbelange Afghanistans in hohem Maße mit der Situation in Pakistan zusammenhängen, 2. Afghanistan durch seinen Beitritt zur SAARC sein Interesse an einer engeren Verbindung mit Südasien demonstriert hat, und 3. Indien als aufstrebende Regionalmacht der einzige regionale Akteur ist, der über die notwendigen Ressourcen, die Entschlossenheit und Legitimität verfügen könnte, um sich langfristig in afghanischen Sicherheitsbelangen zu engagieren.
Keywords: 300